Effects of GH/IGF-I Axis on Retinal Vascular Morphology: Retinal Vascular Characteristics in a Clinical Setting with Severe IGF-I Deficiency. (2nd January 2016) - Taylan Sekeroglu, Hande; Kadayıfcılar, Sibel; Kasım, Burcu; Arslan, Umut; Ozon, Alev
Abstract: Background : The purpose of this study was to assess retinal vascular characteristics of patients with Laron syndrome (LS) as a genetic model of IGF-I deficiency before and after rhIGF1/IGFBP3 treatment and to compare them with healthy controls. Methods : A total of 28 subjects (11 LS, and 17 controls) were enrolled. Patients with LS received combined rhIGF1/rhIGFBP3 1–2 mg/kg/d in a single dose and digital fundus imaging was performed. The number of branching points and tortuosity of retinal vessels were studied. Pre- and post-treatment findings were compared with each other and with controls. Results : The number of branching points was significantly lower in patients with LS in comparison to controls (12.73 ± 3.41, and 17.47 ± 5.82 respectively, p = 0.012). This difference persisted after treatment (12.09 ± 2.66 post-treatment LS versus controls, p = 0.017). Tortuosity indices of nasal arteries (NA) were significantly less in LS than that of controls (upper NA 1.07 ± 0.04 and 1.12 ± 0.06 respectively p = 0.022; lower NA 1.07 ± 0.03 and 1.13 ± 0.07 respectively, p = 0.004). This difference also persisted following treatment ( p < 0.05). Remaining vessels did not differ in tortuosity index. There was no significant difference of tortuosity index and number of branching points before and after treatment in patients with LS. Conclusion : Retinal vascular development may be adversely affected in the setting of severe IGF-I deficiency confirming a major role for GH/IGF-I axis during retinal vascular development in humans antenatally. Resolution of IGF-I deficiency following birth using rhIGF1, however, may not reverse these changes, suggesting that IGF-I may be necessary but insufficient by itself for postnatal angiogenesis.